The Effects of Bariatric Surgery on Diabetic Retinopathy Course: A Review and Meta-Analysis.: Life Sciences-Medicine - Mirghani, Hyder; Ali Alkaabneh, Waad; Mansour Alatawi, Atheer; Abdullah ALQasir, Dhuha; Salem Altemani, Omniah; Talal AlJayani, Rabab (International Journal of Life Science and Pharma Research, 2023)
There is an increasing indication of bariatric surgery for metabolic diseases irrespective of body weight. Diabetic retinopathy is a serious disease; it is the leading cause of registered visual loss globally. Previous literature reported the deterioration of lifethreatening diabetic retinopathy after bariatric surgery. Few studies assessed the same. Our aim of the study is to assess this metaanalysis for the effects of bariatric surgery on diabetic retinopathy remission. In addition, we assessed the effects of bariatric surgery on diabetic retinopathy deterioration. We systematically searched PubMed, Cochrane Library, and the first 100 articles in Google Scholar. The search engine was limited to articles published in English from the first published article up to June 2022. The following keywords were used, bariatric surgery, metabolic surgery, diabetic retinopathy, retinopathy remission, and retinopathy deterioration. The retrieved data were entered in a datasheet detailing the author's name, year and country of publication, the methodology, and the number of patients who deteriorated was stable or improved after bariatric surgery. The most recent RevMan (version 4.4.) was used for data analysis. From our study, we found that, out of the 386 studies screened, only 26 full texts were eligible and eleven studies fulfilled the inclusion and exclusion criteria. A lower deterioration rate was observed than stability, odd ratio, 0.05, 95% CI, 0.04-0.07, P-value, <0.001. Significant heterogeneity was observed, I2=54%, P-value, 0.02, and Chi-square=21.76. in addition, a lower regression was found compared to stable retinopathy, odd ratio, 0.06, 95% CI, 0.03-0.13, P-value, <0.001. Significant heterogeneity was observed, I2=73%, P-value, 0.0002, and Chi-square=29.67. Thus, Diabetic retinopathy remains stable among patients who underwent bariatric surgery. Few remissions were observed in the short term, while few patients deteriorated. Further randomized controlled studies comparing the effect of bariatric surgery and usual diabetic care are needed.